2021
DOI: 10.1021/acscatal.1c02627
|View full text |Cite
|
Sign up to set email alerts
|

Convergent Azaspirocyclization of Bromoarenes with N-Tosylhydrazones by a Palladium Catalyst

Abstract: Azaspirocyclic compounds have gained attention in chemistry and drug discovery fields. In this manuscript, the development of a Pd-catalyzed dearomative azaspirocyclization of bromoarenes bearing an aminoalkyl group with N-tosylhydrazones is described. The present method enables azaspirocyclization with the introduction of carbon substituents, achieving the convergent synthesis of 1-azaspirocycles. This method allowed furan, thiophene, and naphthalene cores to generate the corresponding 1-azaspirocycles. The o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…Our study commenced by screening conditions using 1-bromonaphthalene ( 1A ), N -tosylhydrazone 2a , and p -toluidine ( 3a ) under the influence of a palladium catalyst (Table ). In our previous studies, Pd/DPEphos as well as Pd/ L1 ( L1 : 4-dimethylaminophenyl)­diphenylphosphine) efficiently catalyzed the dearomative 1,4-difunctionalization of bromoarenes . Therefore, as our initial attempt, we conducted the reaction of 1A , 2a , and 3a in the presence of Pd/DPEphos catalyst and Cs 2 CO 3 in toluene at 70 °C.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Our study commenced by screening conditions using 1-bromonaphthalene ( 1A ), N -tosylhydrazone 2a , and p -toluidine ( 3a ) under the influence of a palladium catalyst (Table ). In our previous studies, Pd/DPEphos as well as Pd/ L1 ( L1 : 4-dimethylaminophenyl)­diphenylphosphine) efficiently catalyzed the dearomative 1,4-difunctionalization of bromoarenes . Therefore, as our initial attempt, we conducted the reaction of 1A , 2a , and 3a in the presence of Pd/DPEphos catalyst and Cs 2 CO 3 in toluene at 70 °C.…”
mentioning
confidence: 89%
“…On the other hand, the unique reactivity of π-benzyl palladium species has been unveiled over the past two decades, achieving various bond formations at the C4 position on the aromatic ring. , Among these examples, Bao and Tian have independently developed the C4 amination of benzyl chlorides and ammoniums salts, where a π-benzyl–Pd intermediate reacts with amines to form C–N bonds at the C4 position of arenes (Figure B) . In this context, our group recently reported a dearomative 1,4-difunctionalization of bromoarenes with diazo species and carbon nucleophiles . Merging the C4 C–N bond formation of π-benzyl–Pd species and our three-component reaction, we envisaged that a 1,4-carboamination of bromoarenes with diazo species and amines could be realized (Figure C).…”
mentioning
confidence: 99%
“…11 By capturing these diazo species with transition-metal catalysts, N -tosylhydrazones have been multi-directionally transformed in Z–H (Z = O, NR, S) insertion, 12 cross-coupling, 13,14 and other transformations. 15,16 Given the reactivities of organoborons and N -tosylhydrazones, we envisioned that combining these two functional groups into a single molecule 17 could yield a versatile molecular building block for organic synthesis. In this context, two related examples have recently appeared (Fig.…”
mentioning
confidence: 99%
“…20,25 However, these conditions were not operative for our boryl- N -tosylhydrazone 4 . After exploration of reaction conditions, we found that Barluenga's coupling reaction of 4a with p -tolyl bromide in the presence of Pd 2 (dba) 3 , XPhos, and LiO t Bu in 1,4-dioxane 15 produced desired coupling product 5a in 9% as a mixture of E / Z isomers. In this case, alkyl cyanide 6 was generated as a main product in 79% yield.…”
mentioning
confidence: 99%
“… 2 Among them, transition-metal-catalyzed cross-coupling is one of the powerful protocols for C–X or C C bond formation in organic synthesis involving versatile intermediates, of which in situ generation of diazo compounds and carbene migratory insertion are considered key steps. 3–5 Over the past decades, considerable progress has been made in the asymmetric cross-coupling reactions of N -tosylhydrazones with various coupling partners, including cyclobutanols, terminal alkynes, silacyclobutanes and so on. 4 Relatively, only a few examples focus on the cross-coupling reactions of aryl halides with N -tosylhydrazones involving benzyl metal intermediates [ Scheme 1A , eqn.…”
mentioning
confidence: 99%